Multi-scale patterns in the host specificity of plant-dwelling arthropods: the influence of host plant and temporal variation on species richness and assemblage composition of true bugs (Hemiptera) - Moir, Melinda; Brennan, Karl; Fletcher, M.; Majer, Jonathan; Koch, John (Taylor & Francis Ltd, 2011)
The influence of temporal variation in the host specificity of invertebrates to estimates of biodiversity is rarely considered. While patterns at large spatial scales have stimulated much attention, such comparisons are constrained for southern-hemisphere biomes because the patterning of invertebrates on plants is largely unknown. Here, we analyse variation of plant-dwelling Hemiptera from 15 understorey plant species over 18 months in the south-west Australian biodiversity hotspot. Analyses showed significant interactions in species composition between sampling period and plant species. Fauna that were “effectively specialized” (host-specificity index) to plants changed with season, although this was also related to the number of singletons and overall species richness. Sampling from a single season also overestimated the degree of host specificity by 52% and underestimated the perception of species richness when an outbreak of a particular herbivore occurred. High host-specificity values (12.7 hemipteran species per plant) support the case for high estimates of global arthropod richness.